Studi Literatur: Intervensi Psikologi Klinis Makro terhadap Isu Kesehatan Mental Remaja - Pia Alfia Azis; Mulya Virgonita I. Winta; Shinta Pratiwi (EduInovasi: Journal of Basic Educational Studies, 2025)
Adolescent mental health in Indonesia faces significant challenges, marked by increasing cases of anxiety, depression, and suicide risk. Traditional psychological interventions that focus on individual approaches are considered incapable of addressing systemic root problems. The macro clinical psychology approach is presented as an alternative approach that considers social, cultural, public policy, and broader societal structures. This article aims to review the literature related to macro clinical psychology interventions in the context of adolescent mental health. This study also highlights the challenges of implementation in Indonesia and provides recommendations for sustainable cross-sectoral policies.